Women in the story of Jesus: the gospels through the eyes of nineteenth-century female biblical interpreters - Taylor, Marion Ann; Weir, Heather E. (William B. Eerdmans Publishing Company, 2016)
This volume gathers the writings of thirty-one nineteenth-century women on the stories of women in the Gospels — Mary and Martha, Anna, the Samaritan woman at the well, Herodias and Salome, Mary Magdalene, and more. The selected excerpts represent various literary genres, including commentaries, Scripture biographies, essays, travel diaries, children's lessons, and sermons. Retrieving and analyzing neglected works by Christina Rossetti, Sarah Hale, Elizabeth Wordsworth, and many other nineteenth-century writers, Women in the Story of Jesus illuminates the biblical text, recovers a neglected chapter of reception history, and helps us understand and apply Scripture in our present context. - back of book